Social Media, interaction and advertising. Perception of formats and contents in the web 3.0 - Rebollo Bueno, Sara (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2019)
The main goal of the present study is to obtain conclusions about the advertising contents and formats that help to bring user into social networks. It also analyzes the attitudes community managers should perform, as well as the elements helping to create positive interaction from the users and followers of a brand.To achieve such goals, we developed a method with two qualitative techniques: Firstly, we realized two interviews, one to a University professor who does research on social networks and the other one to a Community manager. Secondly, we carried out six focus groups to people of three different age groups. The first one to people currently between the first and fourth year of secondary school, the second one to people in either the fifth or sixth year of secondary school, and the last one to people enrolled in college. With this we sought to look for a wider range of opinions and likings with respect to the social media beyond a single generation.Among the main conclusions, we find the need for advertisers to have a good combination of offline and online media. Likewise, it is essential on the web 3.0 the creation of a good brand image in the network. It should be noted that the research we made may be useful for future enabling works.
Keywords: social media; advertising; online communication; branded conten; community manager